Are the Responses to Resistance Training Different Between the Preferred and Nonpreferred Limbs?. Issue 3 (March 2016) - Baroni, Bruno M.; Franke, Rodrigo de A.; Rodrigues, Rodrigo; Geremia, Jeam M.; Schimidt, Helen L.; Carpes, Felipe P.; Vaz, Marco A.
Abstract : Abstract: Baroni, BM, Franke, RdA, Rodrigues, R, Geremia, JM, Schimidt, HL, Carpes, FP, and Vaz, MA. Are the responses to resistance training different between the preferred and nonpreferred limbs? J Strength Cond Res 30(3): 733–738, 2016—Humans preferentially recruit limbs to functionally perform a range of daily tasks, which may lead to performance asymmetries. Because initial training status plays an important role in the rate of progression during resistance training, could asymmetries between the preferred and nonpreferred limbs lead to different magnitudes of strengthening during a resistance training program? This issue motivated this study, in which 12 healthy and physically active men completed a 4-week control period followed by a 12-week isokinetic resistance training program, performed twice a week, including 3–5 sets of 10 maximal eccentric contractions for each limb. Every 4 weeks, knee extensor peak torques at concentric, isometric, and eccentric tests were measured using an isokinetic dynamometer and the sum of quadriceps muscle thickness was determined by ultrasound images. Before training, concentric peak torque was similar between limbs but isometric and eccentric peak torques were significantly smaller in the nonpreferred compared with the preferred limb (4.9 and 5.8%, respectively). Bilateral strength symmetry remained constant throughout the training period for concentric tests. For eccentric and isometric tests, symmetry was reached at the fourth and eighth training weeks, respectively. After 12 weeks, between-limb percent nonsignificant differences were −0.62% for isometric and −1.93% for eccentric tests. The sum of knee extensor muscle thickness had similar values before training and presented similar changes throughout the study for both the preferred and the nonpreferred limbs. In conclusion, the nonpreferred limb presents higher strength gain than the preferred limb at the initial phase of an isokinetic resistance training program, and this increased strength gain is not associated with muscle hypertrophy.